Acute and sustained increase in endothelial biomarkers in COVID-19. Issue 4 (4th October 2021) - Méndez, Raúl; González-Jiménez, Paula; Latorre, Ana; Piqueras, Mónica; Bouzas, Leyre; Yépez, Katheryn; Ferrando, Ana; Zaldívar-Olmeda, Enrique; Moscardó, Antonio; Alonso, Ricardo; Reyes, Soledad; Menéndez, Rosario
Abstract : Endothelial injury is related to poor outcomes in respiratory infections yet little is known in relation to COVID-19. Performing a longitudinal analysis (on emergency department admission and post-hospitalisation follow-up), we evaluated endothelial damage via surrogate systemic endothelial biomarkers, that is, proadrenomedullin (proADM) and proendothelin, in patients with COVID-19. Higher proADM and/or proendothelin levels at baseline were associated with the most severe episodes and intensive care unit admission when compared with ward-admitted individuals and outpatients. Elevated levels of proADM or proendothelin at day 1 were associated with in-hospital mortality. High levels maintained after discharge were associated with reduced diffusing capacity.